1998
DOI: 10.1021/jm970842h
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Requirements for Flavone Cytotoxicity and Binding to Tubulin

Abstract: A series of 79 flavones related to centaureidin (3,6,4'-trimethoxy-5, 7,3'-trihydroxyflavone, 1) was screened for cytotoxicity in the NCI in vitro 60-cell line human tumor screen. The resulting cytotoxicity profiles of these flavones were compared for degree of similarity to the profile of 1. Selected compounds were further evaluated with in vitro assays of tubulin polymerization and [3H]colchicine binding to tubulin. Maximum potencies for tubulin interaction and production of differential cytotoxicity profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(87 citation statements)
references
References 45 publications
(99 reference statements)
9
75
0
2
Order By: Relevance
“…Interestingly, it was found that artemetin (3), a close analogue of centaureidin (1), is inactive, and casticin (2) (IC 50 1.286-3.582 μM) containing 3′-hydroxy and 3-methoxy groups, is one order of magnitude less active than centaureidin (1). This finding is in accordance with the observation by Beutler et al (1998) that hydroxy substituents on C-3′ and C-5, and methoxy groups on C-3 and C-4′ are necessary for maximum cytotoxic potency. Casticin (2) reported as a tubulin binding agent and the consequent disturbance in the synthesis of mitotic spindles results in the arrest of cell cycle in G2/M phase.…”
Section: Resultssupporting
confidence: 93%
“…Interestingly, it was found that artemetin (3), a close analogue of centaureidin (1), is inactive, and casticin (2) (IC 50 1.286-3.582 μM) containing 3′-hydroxy and 3-methoxy groups, is one order of magnitude less active than centaureidin (1). This finding is in accordance with the observation by Beutler et al (1998) that hydroxy substituents on C-3′ and C-5, and methoxy groups on C-3 and C-4′ are necessary for maximum cytotoxic potency. Casticin (2) reported as a tubulin binding agent and the consequent disturbance in the synthesis of mitotic spindles results in the arrest of cell cycle in G2/M phase.…”
Section: Resultssupporting
confidence: 93%
“…It has been identified that the C-3 and C-4' methoxy and C-3' and C-5 hydroxy functional groups provide the strong anti-proliferative activity of this flavonoid (18). Casticin exhibits weaker cytotoxicity but greater selectivity than taxol, (the IC 50 of taxol for tumor cells is at the nmol/l level, while the IC 50 of casticin is at the µmol/l level) (19). Although casticin has little or no effect on the apoptosis of normal cells and tissues, it is reported to have an inhibitory effect on the proliferation of malignant tumors (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the presence of a methoxyl group in C-4′ (R3) decreases the toxicity for Vero cells because 3,4′-DMK is less toxic than 3-MK. Beutler et al (1998) compared the cytotoxicity of two flavones on 60 human tumoural strains; 3′-hydroxyl 4′-methoxyl was sixfold more toxic than 3′-methoxyl 4′-hydroxyl. Thus, the nature of the group in C-3′ (R2) and in C-4′ (R3) seems to determine toxicity.…”
Section: Discussionmentioning
confidence: 99%